Duplex microRNAs assay based on target-triggered universal reporter hybridization - Yinan Wang; Yue Sun; Choiwan Lau; Jianzhong Lu (Elsevier, 2018)
In this paper, we designed and evaluated a duplex detection strategy for microRNAs (miRNAs) using universal probe-based target-triggered double hybridization and fluorescent microsphere-based assay system (xMAP array). In the absence of target miRNA, reporter DNA cannot hybridize stably with the immobilized capture DNA due to its low melting temperature. Only after adding target miRNA, can reporter probe hybridize with capture probe to form a stable three-component complex. This target-triggered stable hybridization makes this method possible for highly selective and sensitive detection of multiple miRNAs. We exemplified a quantitative detection of duplex miRNAs with a limit of detection of 40 pM. The xMAP array platform holds the potential of extending this approach to simultaneous detection of up to 100 miRNA targets. Considering the simplicity, rapidity and multiplexing, this work promised a potential detection of multiple miRNA biomarkers for early disease diagnosis and prognosis. Keywords: xMAP array, Multiple microRNAs, Target-triggered, Universal reporter